Evolution of Inclusive Education: A Bibliometric Study of Scopus Data - Nazar, Lailatun; Nursalim, Mochamad; Purwoko, Budi (AS-SABIQUN, 2025)
This research examines the shortcomings of prior studies on global inclusive education trends and patterns. The main objective is to explore and visualize scientific publications on Inclusive Education for Children, as recorded in the Scopus database from 2020 to 2024, using a bibliometric approach. The methodology used is descriptive quantitative analysis through bibliometric techniques. Data were collected by conducting a literature search using the keywords "inclusive education" and "children" in Scopus. These data were then analyzed using VOSviewer software to identify publication patterns, citation trends, and dominant keywords. A significant upward trend in publication output is evident in the results, most notably seen between 2021 and 2022. Frequently occurring keywords include "inclusive education," "human," "teachers," "parents," and "childhood." The main conclusion of this study is that research related to autism spectrum disorders in children has experienced substantial growth in recent years. These findings underscore the need for stronger collaboration among countries to promote a more inclusive approach. This study also contributes to building a foundation for continued scientific research on Inclusive Education for Children.